CircRNA_0058097 promotes tension‐induced degeneration of endplate chondrocytes by regulating HDAC4 expression through sponge adsorption of miR‐365a‐5p. Issue 1 (21st June 2019) - Xiao, Liang; Ding, Baiyang; Xu, Shujuan; Gao, Jianming; Yang, Bijing; Wang, Jing; Xu, Hongguang
Abstract: Excessive mechanical tension can lead to the degeneration of endplate chondrocytes. The presence of tension‐sensitive circRNA_0058097 molecules has been detected in human endplate chondrocytes, where it was found to be a potential competing endogenous RNA. Indeed, inhibiting the expression of circRNA_0058097 effectively enhanced the stress resistance of endplate chondrocytes, suggesting that it may be an important trigger point for the degeneration of endplate cartilage. Through a series of experiments, we reveal that circRNA_0058097 can upregulate the expression of downstream target gene histone deacetylase 4 by sponge adsorption of miR‐365a‐5p, which promoted morphological changes of endplate chondrocytes, and increased extracellular matrix degradation and degeneration of endplate cartilage. Therefore, circRNA_0058097 may provide a new way to prevent and treat endplate cartilage degeneration. Abstract : Excessive intermittent cyclic mechanical tension can induce the degeneration of endplate chondrocytes. Tension‐sensitive circRNA_0058097 can upregulate the expression of downstream target gene histone deacetylase 4 by sponge adsorption of miR‐365a‐5p, which promoted morphological changes of endplate chondrocytes, and increased extracellular matrix degradation and degeneration of endplate cartilage.